2012
DOI: 10.1016/j.trc.2011.09.005
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the factors influencing differences in survey-reported and GPS-recorded trips

Abstract: Recent advances in global positioning systems (GPS) technology have resulted in a transition in household travel survey methods to test the use of GPS units to record travel details, followed by the application of an algorithm to both identify trips and impute trip purpose, typically supplemented with some level of respondent confirmation via prompted-recall surveys. As the research community evaluates this new approach to potentially replace the traditional surveyreported collection method, it is important to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 26 publications
(27 reference statements)
4
53
0
1
Order By: Relevance
“…In addition to that, not all study participants may be familiar with or keen on using electronic devices. Thus, the application of advanced communication technology may result in anxiety and misuse, potentially limiting the applicability of these methods (Bricka et al, 2012).…”
Section: Or the Air Pollution Exposure Distribution Of Adultmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to that, not all study participants may be familiar with or keen on using electronic devices. Thus, the application of advanced communication technology may result in anxiety and misuse, potentially limiting the applicability of these methods (Bricka et al, 2012).…”
Section: Or the Air Pollution Exposure Distribution Of Adultmentioning
confidence: 99%
“…Although functional, there are limits to the general applicability of this methodology due to simplifications and assumptions adopted such as the qualification of indoor activities for which the TAD was used and where the GPS sensor cannot receive a signal. Differences in survey-reported and GPS-reported trips for a 24 hour period were investigated by Bricka et al (2012). Data were selected from the 2009 Indianapolis regional household travel survey.…”
Section: Gps Enabled Personal Monitoringmentioning
confidence: 99%
“…Retrospective questionnaires (asking about individual trips from the previous week without forewarning) provide comparable estimates, but the overall week mileage estimates were 20-30 % lower than trip by-trip listings in most cases. [19] found large differences between IVDR measurements and similar statistics obtained through SR. Bricka et al [4] reported on a study which considered two measures of travel intensity: survey-reported and GPS-recorded. Their findings suggest that the two survey methods complement each other and should be used in tandem.…”
Section: Self-reports (Sr)mentioning
confidence: 99%
“…More specifically, we focused on the relation between these two approaches and on the ability to use them in a complementary manner in order to improve the evaluation of driving behavior. Recent literature suggests the potential strength of combining both technology-based and traditional approaches (see, for example, [4,30]). …”
Section: Introductionmentioning
confidence: 99%
“…Studies comparing self-reported trips from NHTS-style surveys and GPS devices have found that between 10 percent and 35 percent 8 of GPS-identified trips go unreported in surveys (Bricka and Bhat 2006). Not all of the discrepancy is due to survey errors, as some GPS-based methods may be overly sensitive-for example, picking up the walk from an off-site parking lot to the destination as a separate trip or assuming that a long dwell at a traffic signal denotes a gap between two separate trips (Bricka et al 2012). Moreover, some of the underreporting concerns trips by nonmotorized modes, which are particularly difficult to capture in surveys but are not relevant to the analysis here.…”
mentioning
confidence: 99%